Spatial and temporal distribution, geochemical characteristics of carbonatites and their relationship with U–REE mineralization in the Xiaoqinling area, Shaanxi Province - KANG Qingqing; CHEN Zhengle; PAN Jiayong; LI Peng; LIU Yulong; LI Lei; JIANG Hongjun; GAO Cheng (Dizhi lixue xuebao, 2024)
[ Objective ] Carbonatites, as magmatic-origin rocks, are crucial source rocks for uranium, rare earth, and other minerals. They are widely distributed in the Xiaoqinling region of Shaanxi, giving rise to numerous large to super-large carbonatite deposits of uranium, molybdenum, and rare earth, represented by Huayangchuan and Dashigou, attracting attention from scholars in recent years. Previous studies on carbonatite deposits in the area focused on petrology, mineralogy, genesis, and mineralization chronology. However, they were often limited to individual deposits, needing more regional cross-sectional comparative studies. [ Methods ] This study employs field geological surveys, petrographic analysis, and geochemical characterization of typical rocks and ores to reclassify different types and stages of Xiaoqinling carbonatites. It analyzes the geochemical characteristics of various carbonatite types and explores the mineralization processes of uranium and rare earth elements associated with carbonatites. [ Results ] Xiaoqinling carbonatites exhibit a large vein, vein group, and vein network morphology, intruding into the Archean metamorphic basement, Xiong'er Group volcanic sedimentary rocks of the Changchengian System, and Gaoshanhe Group clastic rocks of the Jixianian System along fault structures. Based on field crosscutting relationships and primary mineral assemblage characteristics, Xiaoqinling carbonate rocks can be re-divided into five stages from old to new: aegirine syenite stage (I), aegirine carbonatite stage (II), potassium feldspar carbonatite stage (III), quartz carbonatite stage (IV) and zeolite-bearing carbonatite stage (V). Spatially, the division is roughly along the nearly EW-striking Xiaohe Fault, with northern carbonatite veins dominated by aegirine syenite and aegirine carbonatite, rich in aegirine, biotite and other dark minerals, distributed in the Archean gneiss basement. The southern part is mainly composed of light-colored potassic feldspar carbonatites and quartz carbonatites, almost devoid of dark minerals, with surrounding rocks consisting of Xiong'er Group volcanic sedimentary rocks and Gaoshanhe group clastic rocks. Zeolite-bearing carbonatites are distributed throughout the region. Temporally, the carbonatites formed in the Late Triassic, but distinct temporal differences exist among different sections. Previous data indicate a possible 30 Ma gap in the formation times of various carbonatite types in the Xiaoqinling area. The geochemical characteristics of Xiaoqinling carbonatites reveal an average SiO2 content of 30.43%, significantly higher than the global average for carbonatites. CaO is relatively low, with an average content of 28.71%, exhibiting a clear negative correlation with SiO2 content. Total alkali (Na2O+K2O) content is relatively high, averaging 2.25%, with a maximum value of 10.23%. The total alkali content decreases gradually from early to late stages, strongly correlating with CaO and Al2O3 content. The potassium-sodium ratio (w(K2O)/w(Na2O)) is exceptionally high, with an average of 4.625 and a maximum value of 36.55. Ferromagnesian content (TFe2O3+MgO) varies significantly, with early-stage carbonatites (Stages I, II, III) having higher ferromagnesian content (average 8.29%), while late-stage carbonatites (Stages IV, V) generally have lower ferromagnesian content (average 1.92%). Ferromagnesian content correlates positively with TiO2 content. MnO has an average content of 1.22%, reaching up to 4.49%, notably enriched in late-stage quartz carbonatites. REE content averages 0.26%, with a maximum value of 0.96%, exhibiting a positive correlation with MgO content. The ∑LREE/∑HREE ratio ranges from 0.47 to 27.72, with early-stage carbonatites (Stages I, II, III) showing strong heavy REE depletion. Late-stage quartz carbonatites have an average ∑LREE/∑HREE ratio of 2.15, indicating relatively heavy REE enrichment, especially in Tm, Yb, Lu, and Y. Heavy REE content correlates linearly with MnO content. The overall REE distribution pattern of carbonatites is a steep-left and gentle-right, relatively flat-right-trending model, showing continuous variations in REE distribution patterns throughout different stages. Ore-related element content characteristics of various carbonatite types reveal significant U and Nb enrichment in aegirine syenite, aegirine carbonatite, and potassium feldspar carbonatite. Mo-mineralization is closely associated with potassium feldspar carbonatite and quartz carbonatite, while Pb and Ba-Sr mineralization is evident in all carbonatite stages. [ Conclusions ] (1) Xiaoqinling carbonatites are categorized into aegirine syenites, aegirine carbonatites, potassium feldspar carbonatites, quartz carbonatites, and zeolite-bearing carbonatites in chronological order. (2) Xiaoqinling carbonatites exhibit notably high SiO2 and total alkali content, low MgO content, and exceptionally high potassium-sodium ratio. There is a gradual decrease in CaO, TiO2, Al2O3, ferromagnesian, and total alkali content from early to late stages, while MnO content shows an opposite trend. Carbonatites evolve from early ferrocarbonatite to late calciocarbonatite. (3) Different types of carbonatites show distinct ore-related characteristics, with early stages (aegirine syenite, aegirine carbonatite, and potassium feldspar carbonatite) mainly enriched in U (Nb), and Potassic Feldspar Carbonate additionally enriched in Mo. Late-stage quartz carbonatites are characterized by Mo and HREE enrichment. [ Significance ] The findings of this study provide valuable information for the exploration and research of carbonatite-type uranium, rare earth, and polymetallic deposits in the Xiaoqinling area, holding significant practical importance.